Boric acid as reference substance: pros, cons and standardization - Amorim, M. J. B. (2019)
Boric acid (BA) has been successfully used as reference substance in some standard test guidelines. Due to the fact that previously selected reference substances present a significant risk to human health and/or are banned for environmental reasons, BA is being discussed for broader adoption in OECD or ISO guidelines. To provide input on BA data and contribute to the discussion on its suitability as a reference substance, in the present study BA was tested with two standard soil organisms, Enchytraeus albidus and Folsomia candida, in terms of survival, reproduction and avoidance. Additionally, published data on other organisms was analysed to derive the most sensitive soil dwelling invertebrate (hazard concentration-HC5). Results showed that BA affected the tested organisms, being two times more toxic for collembolans (LC50 = 96; EC50 = 54 mg/kg) than for enchytraeids (LC50 = 325; EC50 = 104 mg/kg). No avoidance behaviour occurred despite the fact that BA affects earthworms. Actually, it is the recommended reference substance for the earthworm avoidance test. Clearly, the suitable performance of BA in one species should not be generalized to other species. Absolute toxicity is not an important criterion for the selection of a reference substance, but it has been proposed that effects should occur within a reasonable range, i.e. <1,000 mg/kg. We could confirm, compiling previous data that for most soil invertebrates, the EC50 is expected to be below 1,000 mg/kg. From these data it could be derived that the most sensitive soil dwelling invertebrate (HC5, 50%) is likely to be affected (EC10) at 28 (8-53) mg H(3)BO(3)/Kg, equivalent to 4.6 (1.4-8.7) mg boron/kg.